The logic of idolatry in seventeenth-century French literature - McClure, Ellen M., 1968- (Gallica (Woodbridge (Suffolk, England)), 2020)
A sensitive investigation into how French writers, including Descartes and Racine, treated a central preoccupation in early modern writings.